Managing energy use in modern buildings : case studies in conservation practice - Flaman, Bernard; McCoy, Chandler; Ostergren, Gail (Conserving modern heritage., 2021)
"Ten case studies address the challenges of improving energy consumption and thermal comfort in modern buildings"--